Mechanisms of the Cardiotoxic Action of Amitriptyline - G. V. Chekmarev; V. T. Dolgikh (Общая реаниматология)
Objective: to study the mechanisms of toxic action of amitriptyline on the myocardium. Material and methods. Investigations were conducted using the hearts from 30 outbred albino rats, which had been isolated and perfused according to the procedure described by Fallen et al. There were two series of experiments: 1) amitriptyline was added in a dose of 250 ng/ml to Krebs-Henseleit solution (Group 1); 2) the agent was added at another concentration (1250 ng/ml) to the solution passing through the coronary bed (Group 2). The animals were anesthetized with thiopental sodium (25 mg/kg) peritoneally. Results. Amitriptyline depresses myocardial contractility, which is particularly obvious with high-rate pacing. This manifests itself as reduced contractile velocity and force-power parameters and elevated left ventricular diastolic pressure. Amitriptyline lowers the efficacy of glucose and increases the release of enzymes into the coronary duct. Conclusion. Hypoergosis, membrane destruction, and cardiomyocyte ion pump failure have been shown to underlie negative chronotropic and inotropic effects in amitriptyline poisoning. Key words: amitriptyline, acute poisoning, isolated heart, myocardial damage.